Epidemiology of Chikungunya virus isolates 2016–2018 in Pakistan. Issue 11 (23rd April 2021) - Badar, Nazish; Ikram, Aamer; Salman, Muhammad; Alam, Muhammad Masroor; Umair, Massab; Arshad, Yasir; Mushtaq, Nighat; Mirza, Hamza Ahmad; Ahad, Abdul; Yasin, Muhammad Talha; Qazi, Javaria
Abstract: The chikungunya virus (CHIKV) is a mosquito‐transmitted alphavirus, which has infected millions of people in Africa, Asia, Americas, and Europe since it remerged in India and Indian Ocean regions in 2005–2006. The purpose of this study was to evaluate the genetic diversity and evolutionary changes in CHIKV from 2016 to 2018 in Pakistan. Blood specimens were collected and processed following the Centers for Disease Control and Prevention Trioplex Protocol. Sequencing and phylogenetic analysis of complete coding sequence of representative isolates from the CHIKV outbreak was carried out during December 2016 to July 2018, a total of 1549 samples were received, out of which 50% ( n  = 774) were found positive for CHIKV RNA. Mean age of chikungunya positive patients was 31.8 ± 15.7 years and most affected were between 21 and 40 years of age. The Pakistan CHIKV strains clustered with the Indian Ocean sublineage of East/Central/South African with cocirculation of some variants In the structural proteins region, two noteworthy changes (A226V and D284E) were observed in the membrane fusion glycoprotein E1. Key substitutions in the neutralizing epitopes site and a few changes indicative of adaptive to other insect cells were also detected in Pakistani strains. This study provides the emerging trend of CHIKV in the country for early identification of potential variants of high virulence and preventive measures for vector borne disease especially in the endemic areas.